Evaluation of efficacy of dinotefuran 20% SG (Token 20% SG) against brown planthopper, Nilaparvata lugens Stal in rice - Jaglan, Maha Singh; Ahlawat, Sushil; Yadav, Jayant (Journal of Cereal Research, 2024)
Rice production is limited by both biotic and abiotic stresses of which insect-pests cause economic losses. Brown planthopper, Nilaparvata lugens Stal is one of the most important sucking insect-pests attacking rice crop throughout the rice growing parts of country, occupies the major status and cause considerable yield damage to the rice cultivation. Various strategies have been employed to manage BPH but insecticides serve as the frontline defense due to their effectiveness and fast action. However, it has now become difficult to manage BPH with the present genre’ of insecticides due to the development of resistance. Besides these chemicals, there is need to test other effective insecticides for management of this pest as there are reports of flare up of this insect. In line dinotefuran 20% SG (Token 20% SG) a new molecule was evaluated under field conditions at CCS Haryana Agricultural University, Rice Research Station, Kaul (Kaithal) to access its efficacy against brown planthopper in rice during kharif, 2020 and 2021. Results revealed that spray of dinotefuran 20% SG (Token 20% SG) @ 40 g a.i. per ha (5–10 hoppers per hill) as the most effective dose in the reduction of hopper population. Non-phytotoxicity of foliar application of dinotefuran 20% SG (Token 20% SG) at doses of 20, 30, 40 and 50 g a.i. per ha to rice crop has also been observed. This chemical is also relative safety to the natural enemies (spiders, mirid bugs and coccinellids) under field conditions. Maximum grain yield (44.4 & 46.8 q per ha) was observed in the dinotefuran 20% SG (Token 20% SG) in spray @ 50 gm a.i. per ha during both the seasons, respectively which was at par with its lower dose @ 40 g a.i. per ha. At harvest, the residues of dinotefuran 20% SG (Token 20% SG) at recommended (40 g a.i. per ha) and double recommended doses (80 g a.i. per ha) were below the detectable level in soil, rice straw and grain.